Laboratory-Cultured Strains of the Sea Anemone Exaiptasia Reveal Distinct Bacterial Communities - Herrera, Marcela; Ziegler, Maren; Voolstra, Christian R.; Aranda, Manuel (Frontiers in Marine Science, 2017)
Exaiptasia is a laboratory sea anemone model system for stony corals. Two clonal strains are commonly used, referred to as H2 and CC7, that originate from two genetically distinct lineages and that differ in their Symbiodinium specificity. However, little is known about their other microbial associations. Here, we examined and compared the taxonomic composition of the bacterial assemblages of these two symbiotic Exaiptasia strains, both of which have been cultured in the laboratory long-term under identical conditions. We found distinct bacterial microbiota for each strain, indicating the presence of host-specific microbial consortia. Putative differences in the bacterial functional profiles (i.e. enrichment and depletion of various metabolic processes) based on taxonomic inference were also detected, further suggesting functional differences of the microbiomes associated with these lineages. Our study contributes to the current knowledge of the Exaiptasia holobiont by comparing the bacterial diversity of two commonly used strains as models for coral research.